Structural and Compositional Responses to Thinning over 50 Years in Moist Forest of the Northern Rocky Mountains. Issue 5 (8th May 2019) - Shen, Chenchen; Nelson, Andrew S; Jain, Terrie B; Foard, Meghan B; Graham, Russell T
Abstract: A thinning study was established in 1967 in moist mixed forests on the Priest River Experimental Forest in northern Idaho, USA. The study design included three thinning intensities: low, moderate, and high intensity (1, 976, 988, and 494 trees ha –1 ). This study examined short-term (11 years) and long-term (50 years) thinning effects on residual stand characteristics, growth, and yield. Since regeneration may occur after thinning, understory change was also addressed. Thinning decreased stand density immediately but improved the growth of residual trees. Shade-tolerant species were favored in all the thinnings and dominated 50 years after thinning. Unthinned stands had higher total and merchantable volume than all thinned stands both 11 years and 50 years post treatment. Regeneration and nontree vegetation richness increased shortly after thinning, whereas nontree vegetation cover decreased sharply 50 years after treatment. The stands developed into multistrata forests with shade-tolerant species in both the overstory and understory. This is contrary to current thinning practice favoring shade-intolerant species, but demonstrates the resilience of moist Northern Rockies forests to partial overstory disturbances. In this study, thinning favoring shade-tolerant species in these mixed forests has a more significant effect on forest structure dynamics than timber production.